COMPARISON OF PRIMARY WOUND CLOSURE WITH DELAYED PRIMARY CLOSURE IN PERFORATED APPENDICITIS - Ahmad, Mukhtar; Ali, Kishwar; Latif, Humera; Naz, Saman; Said, Khalid (Journal of Ayub Medical College Abbottabad, 2014)
Background: Delayed primary closure in cases of acute appendicitis is debated among the surgeons as to whether it decreases the rate of wound infection in comparison to primary closure. The aim of this study was to find out the optimal method of wound closure in cases of perforated appendicitis. Methods: This randomized control trial was conducted at the surgical units of Ayub Teaching Hospital Abbottabad from May to November 2012. A total of 158 patients having perforated appendicitis were included in the study. They were randomly divided two groups. The wounds were primarily closed in one group and left open with daily saline soaked dressing, to be closed on postoperative day 4 in case of the other group. The main outcome measure was wound infection. A wound was considered infected if it was discharging pus, was red and swollen on postoperative day 8th. The method of wound closure was considered efficacious if there was no wound infection till 8th postoperative day. Results: A total of 158 patients, 56 (35.4%) male and 102 (64.6%) female were included in the study. Primary closure group had a total number of 79 patients with 26 (32.9%) male and 53 (67.1%) female. Delayed primary group had also a total number of 79 patients with 30 (38%) male and 49 (62%) female. The mean age of patients in the primary closure group was 26.67±7.32 years while in the delayed primary group was 28.15±6.88 years. In the entire series, 36 (22.8%) patients developed wound infection. There was a significant association between wound infection and type of skin closure (Delayed Primary Closure 6.3% vs. Primary Closure 39.2%, p<0.000). Conclusion: Delayed Primary closure is the optimal management strategy in case of perforated appendicitis as it decreases the incidence of wound infection. Keywords: Delayed primary closure, primary closure, perforated appendicitis, wound, infection